Wordwall as English for Young Learner Instructional Material to Augment Motivation - Jayanti, Widya Mas Mardavam; Indriani , Lilia (STAIN Majene, 2024)
In the 21st century, the necessity of innovative teaching materials has become increasingly apparent to foster students' learning motivation. Teaching English to young learners poses a significant challenge, and educators must employ technology to create engaging instructional materials to cater to the needs of the alpha generation. Wordwall is a digital application that offers a variety of quizzes and games that teachers can utilize to enhance the teaching and learning process. The primary objective of this study was to augment the learning motivation of students enrolled in private tutoring centers. A qualitative approach was adopted in this investigation, with observation, questionnaire, and interviews serving as supplementary methods. The findings revealed that students' perceptions shifted after exposure to Wordwall-based instruction. The findings further suggested that integrating Wordwall could enhance students' learning motivation while reducing boredom and saturation during the learning process. Consequently, it holds the potential to alleviate student ennui and monotony. Moreover, the utilization of Wordwall has been observed to positively impact students' motivation to learn, making it one of the user-friendly interactive media that can augment students' motivation to learn English in the classroom.